Effects and Mechanism of Salvianolic Acid B on the Injury of Human Renal Tubular Epithelial Cells Induced by Iopromide - Dong, Shu-Jun; Gao, Xin-Yue; Pei, Ming-Xin; Luo, Ting; Fan, Dong; Chen, Yan-Ling; Jin, Jun-Feng; Zhao, Xiao-Duo (Frontiers in Pharmacology, 2021)
With the increasing application of medical imaging contrast materials, contrast-induced nephropathy (CIN) has become the third major cause of iatrogenic renal insufficiency. CIN is defined as an absolute increase in serum creatinine level of at least 0.50 mg/dL or an increase >25% of serum creatinine from baseline after exposure to contrast. In this experiment, the protective effects of salvianolic acid B (Sal B) were detected in human renal tubular epithelial cells (HK-2) exposed to iopromide. The results showed that different concentrations of Sal B counteracted the loss of cell viability induce by iopromide, reduced cell apoptosis, the ROS levels, the endoplasmic reticulum stress (ERS)-related and apoptosis-related proteins levels such as p-IRE-1α, p-eIF-2α/eIF-2α, p-JNK, CHOP, Bax/Bcl-2, Cleaved Caspase-3. In addition, Sal B at a concentration of 100 μmol/L could inhibit the ERS and reduce cell damage which was similar to the ERS inhibitor 4-PBA. More importantly, the treatment with ERS agonist Tunicamycin (TM) can abolish the protective effects of Sal B, reducing cell viability and MMP, increasing ROS levels and the expression of Bax/Bcl-2, Cleaved Caspase-3, GRP78, p-eIF2α, p-JNK, and CHOP significantly. These results suggested that the protective effect of Sal B against HK-2 cells injury induced by iopromide may be related to the inhibition of ERS.